2014
DOI: 10.1186/1471-2105-15-s4-s1
|View full text |Cite
|
Sign up to set email alerts
|

Integrated assessment of predicted MHC binding and cross-conservation with self reveals patterns of viral camouflage

Abstract: BackgroundImmune recognition of foreign proteins by T cells hinges on the formation of a ternary complex sandwiching a constituent peptide of the protein between a major histocompatibility complex (MHC) molecule and a T cell receptor (TCR). Viruses have evolved means of "camouflaging" themselves, avoiding immune recognition by reducing the MHC and/or TCR binding of their constituent peptides. Computer-driven T cell epitope mapping tools have been used to evaluate the degree to which particular viruses have use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 32 publications
3
41
0
Order By: Relevance
“…Indeed, recent analyses indicated that Epstein-Barr virus and cytomegalovirus contained fewer T cell epitopes and exhibited higher crossreactivity with the human genome than did either Ebola or Marburg virus [14]. Ebola and Marburg viruses, on the other hand, were composed of significantly fewer peptide sequences that were crossreactive with human and expressed a larger number of predicted T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, recent analyses indicated that Epstein-Barr virus and cytomegalovirus contained fewer T cell epitopes and exhibited higher crossreactivity with the human genome than did either Ebola or Marburg virus [14]. Ebola and Marburg viruses, on the other hand, were composed of significantly fewer peptide sequences that were crossreactive with human and expressed a larger number of predicted T cell epitopes.…”
Section: Discussionmentioning
confidence: 99%
“…JanusMatrix, a new bioinformatics tool, interrogates a potential T cell epitope from both its HLA-binding and TcR-facing aspects, and assesses TcR cross-reactivity with T cell epitopes encoded by other genomes [13,14]. Those epitopes from two different genomic sources, e.g., HCV and human, that bind the same HLA molecules and present identical amino acids to the TcR are designated potentially cross-reactive, capable of stimulating the same TcR and triggering the same T cells to respond.…”
Section: Janusmatrix Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Homology to the human genome was recently discovered in some commensal viruses using the same tool, and was found to differ quite significantly from the level of homology to self for 'hit-and-run' viruses like Variola, Ebola, and Marburg. 64 In reality, TCRs are able to recognize their target epitopes by AA residue side-chain availability; this means that JanusMatrix cannot predict all putative cross-reactive epitopes derived from the human genome based on sequence similarity alone, however it can still help narrow down the set of epitopes that would be later tested experimentally to prove whether or not they trigger suppressive or autoimmune responses. 21 For our predicted HLA class I set, we stringently selected only the epitopes with zero cross-reactive hits in the human genome.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the collaborating groups at EpiVax and iCubed discovered epitopes that activate T regulatory cells (Tregs) in viral pathogens using the JanusMatrix tool. 24,[34][35][36] Epitope-driven vaccines designed using the iVAX toolkit have been tested using a number of new delivery methods that will also be reviewed below.…”
Section: Computational Vaccinologymentioning
confidence: 99%